Marketing 5.0 : technology for humanity - Kotler, Philip; Kartajaya, Hermawan, 1947-; Setiawan, Iwan (Hoboken, New Jersey : Wiley, 2021)
"Famous for inventing 'The 4 P's of Marketing' Professor Phil Kotler's textbooks have trained generations of marketers in the basics of this challenging discipline. In Marketing 5.0 he explains the greatest problem facing marketers today how to integrate three major movements that are changing global markets and customer behavior: Dramatic advances in technology such as AI, Sensors, and the Internet of Things, which are enabling extreme forms of customer targeting and personalization; Dramatic shifts in customer behavior, such as Whatever-Whenever-Wherever (WWW) and the differences between Generations X, Y, Z, and Alpha; And dramatic shifts in business models such as Everything as a Service, Physical/Digital business models. His solution to integrating these challenging forces is Technology for Humanity--finding ways to use technology to advance Customers' non-material needs, and satisfy material desires in ways that also uplift the human spirit, and honor larger human goals, such as justice and environmental protection. Marketers are struggling to cope with the digital transformation of business and the changing behavior of customers. Marketing 5.0 explains how marketers can use technology to address customers' deepest needs, and make a difference."--
Includes index.
Keywords: Marketing; Technology